Isolation and Identification of Flavonoid Compounds from Mahogany Leaves (Swietenia mahagoni) and Their Antioxidant Activity with the DPPH Method (Indonesian Journal of Chemical Science, 2022)
Mahogany leaves (Swietenia mahagoni) contain antioxidant compounds such as alkaloid, flavonoid, steroid, terpenoids, and tannin. This study aims to analyze the types of flavonoid compounds and the strength of IC50 in mahogany leaves (Swietenia mahagoni). The independent variables in this study were the type of sample and the concentration in the antioxidant test. The control variables used are solvent volume and extraction time. While the dependent variable is the IC50 value. The isolation methods used were maceration extraction, partitioning, TLC, and separation using column chromatography. Samples were characterized using GC, FT-IR, and UV-Vis. The presence of flavonoids was proven by using the FT-IR instrument where there was the absorption of the functional groups OH, aliphatic CH, C=O, C=C aromatic, C-O, and CH aromatics. UV-Vis spectrophotometer showed absorption with a maximum wavelength of 230 in band 2 and 408 in band 1. It can be assumed that the isolated flavonoid compound was an Auron-type flavonoid. The IC50 in the methanol extract was 48.07 ppm at various concentration (45.83; 62.50; 79.16) ppm, the ethyl acetate fraction was 38.26 ppm at various concentration (12.50; 45.83; 79, 16) ppm, positive isolates of flavonoid mahogany (Swietenia mahagoni) 70.00 ppm at various concentration (75.00; 100.00; 125.00) ppm, and quercetin 30.384 ppm at various concentration (45.83; 50.00 ; 66.67) ppm.